Associations between social participation and subjective quality of life for adults with moderate to severe traumatic brain injury. (August 2014) - McLean, Alison M.; Jarus, Tal; Hubley, Anita M.; Jongbloed, Lyn
Abstract Purpose: To examine the association between social participation and subjective quality of life (SQOL) for non-employed, community-dwelling adults with moderate to severe traumatic brain injury (TBI) at 1 year or greater post-injury. Method: A correlational study was conducted involving 46 participants. Social participation was measured using the Community Integration Questionnaire, Social Provisions Scale and the Adult Subjective Assessment of Participation. SQOL was measured using the Quality of Life and Health Questionnaire, Abdel-Khalek Happiness Scale and UCLA Loneliness Scale. Results: Higher levels of happiness and global quality of life were each associated with higher levels of enjoyment, satisfaction with performance and higher proportion of activities performed with others. Lower levels of loneliness were associated with higher levels of general social integration and higher levels of perceived social supports. There were no associations found between SQOL and the objective social participation measures of diversity, frequency (intensity) or proportion of activities performed outside of home. Conclusions: Findings contribute to the TBI literature in showing that it is: (a) the more subjective and not objectively measured nature of participation that is associated with SQOL and (b) positive and negative aspects of quality of life show different relationships with social participation variables. Implications for Rehabilitation A high proportion of individuals with traumatic brain injury (TBI) experiences reduced involvement in social participation (involvement in social and leisure activities and within a social network) and low subjective quality of life (SQOL). This study suggests that, by simply increasing the variety and frequency of social and leisure activities, there may be no positive influences on SQOL. Instead, this study suggests that, to increase SQOL, it is important to increase opportunities for individuals to participate with others and also to enhance their subjective experience of social and leisure activities. The large variance obtained of scores for social participation and SQOL provide a reminder to clinicians to maintain an individualized approach when working with individuals with TBI.